The economic importance of the services sector iinternational and local level - Redif, Moustafa; Smaail, Mourad (Milev Journal of Research and Studies, 2018)
Among the most important changes that have taken place in the business world in recent times is the increasing interest in the services sector compared to other sectors, which is one of the types of industries that require large operations and planning compared to the manufacture of physical products, and because of its effective role in the economies of countries such as developed or developing countries such as Arab countries. What we will try to highlight in this article by defining the services sector and exposure for reasons of international growth and then clarify the process of commercial liberalization by the GATS and then exposure to its economic importance internationally and Arab, we have finally concluded that the service sector is really important in the economy countries but remain different ratios.